Electrophysiological findings in Fabry cardiomyopathy: mapping the maze of risk stratification - Li, Jin; Warth, Arne; Schnabel, Philipp Albert; Schweizer, Patrick Alexander; Buß, Sebastian Johannes; Steen, Henning; Becker, Rüdiger; Katus, Hugo; Thomas, Dierk (Acta cardiologica, 2012)
We report a case of Anderson-Fabry disease in a young man presenting with cardiac hypertrophy and asymptomatic non-sustained ventricular tachycardia. The patient was referred for evaluation of implantable cardioverter/defibrillator therapy. Assessment of left ventricular ejection fraction is considered the gold standard for identifying patients at risk of sudden cardiac death. However, this patient’s left ventricular function was preserved. Electrophysiological study did not reveal inducible arrhythmia or cardiac conduction abnormalities. Review of the literature indicates limited knowledge on the electrophysiology of Fabry cardiomyopathy and highlights the need for optimized risk stratification strategies.
Published online: 23 May 2017
Gesehen am 29.10.2018